2010
DOI: 10.1002/jid.1641
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of a green revolution in Africa—the case of Ghana

Abstract: Agricultural growth in Africa has accelerated, yet most of this growth has been driven by land expansion. Land expansion potential is reaching its limits, urging governments to shift towards a green revolution type of productivity-led growth. Given the huge public investments required, this paper aims to assess the potential impacts of a green revolution.Results from a CGE model for Ghana show that green revolution type growth is strongly propoor and provides substantial transfers to the rest of the economy, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Given the relatively small size of the yield improvements needed to offset climate change damages, we conclude that raising crop yields is likely to be an effective adaptation option for Ghana. Moreover, this adaptation option is consistent with Ghana's existing development objectives of reducing rural poverty [20]. There are more modest reductions in the welfare losses caused by climate change when adaptation policy is directed towards either increasing irrigation coverage or diversifying energy supply.…”
Section: Adaptation Policiesmentioning
confidence: 53%
“…Given the relatively small size of the yield improvements needed to offset climate change damages, we conclude that raising crop yields is likely to be an effective adaptation option for Ghana. Moreover, this adaptation option is consistent with Ghana's existing development objectives of reducing rural poverty [20]. There are more modest reductions in the welfare losses caused by climate change when adaptation policy is directed towards either increasing irrigation coverage or diversifying energy supply.…”
Section: Adaptation Policiesmentioning
confidence: 53%
“…However, many studies have found that such interventions through formal research institutions generally do not necessarily provide farmers with more secure access to new technologies or improve their livelihoods (Van de Fliert and Braun, 2002;Waters-Bayer et al, 2004;Hoffmann et al, 2007). In particular, agricultural research in Africa has failed to provide useful outputs to poor smallscale producers (Mosley, 2002;Sumberg and Reece, 2004;Breisinger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, agricultural growth has been shown to be an important driver of poverty reduction and job creation, especially among the rural poor (Diao et al 2007;World Bank 2008;Breisinger et al 2011). In addition, if agricultural development can improve the allocation of resources within households, it will likely lead to better health and nutrition outcomes for children as well (Duflo 2012).…”
Section: Introductionmentioning
confidence: 99%